(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The importance of architectural competitions at the professional and academic levels, as Competitions have been adopted across multiple time periods to find a variety of solutions to design problems and achieve non-traditional building patterns that promote creativity, And contributes to the creation of the best designs and the introduction of new trends reflected directly in the formation of the built architectural environment and in order to achieve upgrading and development In addition to its educational importance in terms of combining architectural theory and the practical practice of both engineers and architecture students, they are intellectual meetings that contribute to stimulating self-learning and encouraging creativity through investigation and competition to develop skills and enrich information. This research is interested in architectural competitions at the academic level, as it was addressed by previous studies and thesis through the description as an experimental tradition and social technologies and a research tool to achieve a scientific goal of learning and achieving creativity, as well as referring to it as one of the types of informal learning in architecture, with Note that architectural competitions in academic education have been referred to implicitly in all international studies. While it was not mentioned in Arab and local studies, the problem of research was identified by the limited knowledge associated with academic architectural competitions and their types, in general, and in fact local in particular, to be the goal of the research to define these competitions and identify the most important types and in order to contribute to enhancing the importance of Adopted in local architectural academies, this goal has necessitated the adoption of the descriptive analytical approach to previous studies and knowledge from inside and outside the field of architecture. The research problem was determined by the limited knowledge associated with academic architectural competitions and their types, in general, and in local reality in particular, the aim of the research is to define those competitions and identify the most important types and contribute to enhancing the importance of its adoption in the local architectural academies, In addition to the applied experiments associated with it, to apply to the application on specific case study represented by Tamayouz Award with four categories, the research assumed the possibility of the academic architectural competition to include several types and in accordance with the requirements of the organizer and its endeavor to contribute to the promotion of the process Learning education in architectural academies, according to which the results are analyzed and conclusions and recommendations formulated.